2009
DOI: 10.4049/jimmunol.0902096
|View full text |Cite
|
Sign up to set email alerts
|

Signal-Transducing Adaptor Protein-2 Regulates Stromal Cell-Derived Factor-1α-Induced Chemotaxis in T Cells

Abstract: Signal-transducing adaptor protein-2 (STAP-2) is a recently identified adaptor protein that contains pleckstrin and Src homology 2-like domains, as well as a YXXQ motif in its C-terminal region. Our previous studies revealed that STAP-2 regulates integrin-mediated T cell adhesion. In the present study, we find that STAP-2 expression affects Jurkat T cell migration after stromal cell-derived factor-1α (SDF-1α)-treatment. Furthermore, STAP-2-deficient T cells exhibit reduced cell migration after SDF-1α-treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 42 publications
4
60
0
Order By: Relevance
“…Thus, our data suggest a strong involvement of STAP-2 in the linkage of BCR-ABL and CXCR4. Coupled with our previous results indicating that STAP-2 enhances SDF-1a signaling through interactions with Vav (Sekine et al, 2009a), STAP-2 is likely to regulate SDF-1a/CXCR4 at multiple levels in CML cells. Therefore, STAP-2 is likely to play a crucial role in the pathogenesis of CML.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Thus, our data suggest a strong involvement of STAP-2 in the linkage of BCR-ABL and CXCR4. Coupled with our previous results indicating that STAP-2 enhances SDF-1a signaling through interactions with Vav (Sekine et al, 2009a), STAP-2 is likely to regulate SDF-1a/CXCR4 at multiple levels in CML cells. Therefore, STAP-2 is likely to play a crucial role in the pathogenesis of CML.…”
Section: Discussionsupporting
confidence: 86%
“…In this study we demonstrated that STAP-2 interacts with and modifies the function of various signaling or transcription molecules Yamamoto et al, 2003;Sekine et al, 2005Sekine et al, , 2006Sekine et al, , 2007bSekine et al, , 2009a. We also demonstrated that BCR-ABL acts as a novel binding partner for STAP-2 in the presence of both the STAP-2 SH2-like domain and STAP-2 Tyr250 phosphorylation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…STAP-2 is expressed in a variety of tissues and cells, such as lymphocytes, macrophages, and hepatocytes (9), and its abundant expression pattern suggests that STAP-2 influences a variety of signaling or transcriptional molecules. Indeed, we previously reported that STAP-2 can modulate the transcriptional activity of STAT3 and STAT5, as well as TLR-mediated signals in macrophages and integrin-or SDF1a-mediated signals in T cells (9,(11)(12)(13)(14). Through these interactions, STAP-2 plays physiological roles in immune responses.…”
mentioning
confidence: 99%